A new species of Tillandsia (Tillandsioidae, Bromeliaceae) from the high Andean forests near Bogotá (Colombia) - Aguirre-Santoro, Julián; Hernández-A., Érika; Hernández-Rodríguez, David E.; Betancur, Julio (Phytotaxa, 2023)
A new species of Tillandsia from high elevation forests of the Eastern Cordillera of Colombia is described here: Tillandsia chingacensis. This species is unique because of its floral parts densely covered with a resin-like substance, and exceptionally long fruits. Although this species has distichous flowers and bears petal appendages, it was not placed in Vriesea because it shows morphological affinities to species of Tillandsia subg. Allardtia, suggesting a better placement of this taxon in Tillandsia. The discovery of this species is the result of recent explorations to a former war zone in the proximity of Bogotá (Colombia). This novelty demonstrates that further scientific expeditions to these areas recently opened for exploration will bring numerous taxonomic discoveries for Colombia. Finally, the description of this new species is complemented with notes on its geographical distribution, habitat, conservation status and a discussion of its taxonomic affinities.